Tuning the properties of F:SnO2 (FTO) nanocomposites with S:TiO2 nanoparticles – promising hazy transparent electrodes for photovoltaics applications. Issue 1 (12th December 2016) - Zhang, Shan-Ting; Foldyna, Martin; Roussel, Hervé; Consonni, Vincent; Pernot, Etienne; Schmidt-Mende, Lukas; Rapenne, Laetitia; Jiménez, Carmen; Deschanvres, Jean-Luc; Muñoz-Rojas, David; Bellet, Daniel
Abstract : Fabrication and innovative characterization of new hazy S:TiO2 –FTO nanocomposites with lower R s thanks to the conductive S:TiO2 nanoparticles. Abstract : The appropriate choice of nanoparticles is proved to be essential in tuning the properties of F:SnO2 (FTO) nanocomposites. With the use of more conductive sulphur-doped TiO2 (S:TiO2 ) nanoparticles, the sheet resistance of S:TiO2 –FTO nanocomposites is successfully reduced down to 38% as compared to the standard flat FTO (11.7 Ω sq −1 ), while the haze factor of the S:TiO2 –FTO nanocomposites can be varied from almost zero (reference flat FTO) up to 60%; moreover the majority of 〈110〉 oriented S:TiO2 nanoparticles leads to a strong (110) texture in the resulting S:TiO2 –FTO nanocomposites by local epitaxy. Careful morphology analyses and angle-resolved measurements reveal that the haze factor is proportional to the total surface coverage of the S:TiO2 nanoparticle agglomerates, while the feature size of the agglomerates determines the angular distribution of the scattered light – this is confirmed by an angle-resolved Mueller matrix polarimeter which allows obtaining the optical microscopic and angle-resolved images of the exact same textured region. Our work establishes the guidelines to fabricate FTO and other transparent conductive oxide (TCO) nanocomposites as promising electrodes in solar cells with tunable structural, electrical, and optical properties.